Designing Neutron Shield Material for D-T Neutron Generator. Issue 1 (January 2021) - Li, Xianglong; Cong, Meilin; Yang, Guifu; Su, Weihua
Abstract: If hydrogen-rich material is used to shield the 14 MeV neutrons produced by D-T neutron generator whose neutron yield is 10 8 n/s, its thickness must be more than 74 cm to make dose of neutron radiation less than 0.025 mSv/h. For decrease the thickness, two layers material composed of boron-polyethylene and copper used as 14 MeV neutron shielding material. The calculation result shows that the minimum thickness of the two layers material is 52 cm, in which the thicknesses of copper and boron-polyethylene are 38 cm and 14 cm and the boron concentration is 1.00%.